Rapid evidence profile report #93: Examining the potential causal relationship between stress and multiple sclerosis - Bain, T; Dass, R; Wu, N; Chen, K; Grewal, E; Ciurea, P; Sivanesanathan, T; Ali, A; Wilson, MG (My University, 2025)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about the potential causal relationship between stress and multiple sclerosis in response to a decision-maker’s request.
Keywords: causal; stress; multiple sclerosis